Antennal sensory organs and glands of the harlequin ladybird, Harmonia axyridis. Issue 1 (6th July 2020) - Sevarika, Milos; Rondoni, Gabriele; Conti, Eric; Romani, Roberto
Abstract: Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) is a sub‐cosmopolitan species. Native to Asia, it has been released during the 20th century for classical and augmentative biological control of several herbivorous insects, mostly aphids and coccids. Despite its recognized positive impact on biological control, H. axyridis is now considered among the most dangerous invasive species in Europe and in most places where it has established. This is mostly due to its ability to reduce the populations of native predatory species of the same trophic guild. When exploring a new area, H. axyridis adults use semiochemical cues to acquire information about the habitat. Presumably, these cues are perceived by the sensilla located on the antennae. Surprisingly, in spite of the huge literature existing on H. axyridis, the antennal sensory organs have been poorly characterized. Here, we used scanning and transmission electron microscopy (SEM, TEM) techniques to study H. axyridis antennae, with focus on the various types of sensilla and their distribution in male and female individuals. The presence of various classes of antennal sensilla belonging to the main types described in insects (chemoreceptors, mechanoreceptors, and thermo‐hygroreceptors) was highlighted, as well as the widespread presence of antennal glands. The investigations showed some peculiar characteristics not known in Coccinellidae, such as the concentration of sensory structures at the level of the distal part of the apical antennomere and the discovery of antennal glands associated with it. No sexual dimorphism was revealed, neither for the general structure of the antenna (similar number of antennomeres and presence of modifications), nor for the total length and width of the antenna, the relative size of the antennomeres, the types of antennal sensilla, of their distribution and abundance. The potential relevance of these sensory structures and antennal glands, reported for the first time in Coccinellidae, is discussed in the context of intra‐ and interspecific communication. Abstract : We conducted a detailed study of Harmonia axyridis (Coleoptera: Coccinellidae) antennae, with reference to the various types of sensilla and their distribution in males and females. Investigations were performed using scanning and transmission electron microscopy techniques. The analysis allowed us to highlight the presence of various classes of antennal sensilla, as well as associated antennal glands, described for the first time in Coccinelidae. Their potential relevance is discussed in the context of intra‐ and interspecific communication.